Model Sosialisasi Kearifan Lokal Masyarakat Baduy dalam Pelestarian Hutan Kepada Generasi Muda di Kampung Balimbing, Baduy Luar - Nasution, Isman Pratama; Permana, R. Cecep Eka; Sulistyowati, Dian (UI Scholars Hub, 2014)
The Baduys are rice farming communities who rely on nature and the forest. Therefore, they keep and maintain their forests through customs and cultural practices. Dudungusan is preserved forest, prohibited for cultivation. Garapan is the land that can be processed into fields (huma), following the needs and rules of cultivation. Although the Baduys live in groups in small villages at the foot and slopes of hills or mountains, they keep and follow their local wisdom. This is evident from the review and the community activities that have been done earlier. There are records of the knowledge, views, and understanding of the old and young Baduys about forest conservation and identifying existing problems. The method used is the dissemination and sharing of knowledge. The results of the data collection and identification of the reference model of socialization, or carean, are used to understand the local knowledge about forest conservation. The Baduy residents in Kampong Balimbing who are involved in the research are the kokolot, or the class of older generation, whereas the youth group are participating in the process. In general, the activity is well-shared for both for the older and younger generation. In addition to this, the residents of other Baduy villages may learn from Kampong Balimbing’s wisdom.